2012
DOI: 10.1121/1.3679004
|View full text |Cite
|
Sign up to set email alerts
|

Broadband acoustic concentrator with multilayered alternative homogeneous materials

Abstract: A two-dimensional cylindrical acoustic concentrator is designed with multilayered alternative homogeneous materials, which can focus acoustic field and enhance acoustic energy in a given area. The frequency response analysis of the acoustic concentrator demonstrates that the acoustic energy can be concentrated within the device over a wide frequency band. Meanwhile, there are contradictory relations between the acoustic concentrating performances in the inner region and the scattering properties in the outer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…As can be seen from Fig.5, different shape concentrators are achieved without changing the materials of Eq. (6) and their results exhibit strong agreement with their previous counterparts which were achieved by performing tedious calculations [12][13][14][15].…”
Section:  supporting
confidence: 84%
“…As can be seen from Fig.5, different shape concentrators are achieved without changing the materials of Eq. (6) and their results exhibit strong agreement with their previous counterparts which were achieved by performing tedious calculations [12][13][14][15].…”
Section:  supporting
confidence: 84%
“…The process can also be reversed: one can place a source at the focus and convert a cylindrical wavefront generated by a point source into a plane wavefront. Similar work on designing acoustic concentrators using transformation acoustics has been recently reported in Wang et al 16 Previously, Rahm et al 17 reported the design of electromagnetic concentrators.…”
Section: B Transformations Yielding Power Law Radial Stiffness K Rmentioning
confidence: 73%
“…2 a straight lines and dotted lines. This characteristic is the main difference comparing to the previous Wang’s design 23 which used normal transformation method. The density tensor and bulk modulus for the Ref.…”
Section: Methodsmentioning
confidence: 80%
“…And by applying acrylonitrile butadiene styrene plastic structure, they constructed it physically. Then, more researches about acoustic concentrators 22 , 23 and rotators 21 , 24 , 25 emerged, that can magnify the intensity or rotate the propagation direction of the acoustic wave in the internal region and keep external field unchanged. However, the physical realization of the acoustic concentrators and rotators suffers from complicated parameters, especially inhomogeneity, making it difficult for experimental realization.…”
Section: Introductionmentioning
confidence: 99%